Left Ventricular Ejection Fraction among Patients with Acute Myocardial Infarction: Left Ventricular Ejection Fraction: Acute Myocardial Infarction - Nayyar, Maheer; Iqbal, Zafar; Ashraf, Zubair; Saigol, Naif Usman; Choudhary, Usman Ghani; Shahzad, Naeem; Tariq, Ayesha (Pakistan Journal of Health Sciences, 2026)
After an acute myocardial infarction (AMI), the LVEF may be used for prognosis and therapy purposes. Despite the importance of left ventricular ejection fraction (LVEF) testing as a performance indicator for AMI patients, nothing is known about the current rates of in-hospital assessment or how it relates to therapeutic utilization. Objective: To ascertain the prevalence of LVEF patterns in individuals with AMI. Methods: It was a cross-sectional descriptive study conducted at the Department of Cardiology, King Edward Medical University/ Affiliated Hospital, Lahore, from March 2025 to September 2025 under IRB number 783/RC/KEMU. A total of 110 patients were enrolled through nonprobability purposive sampling. Data analysis was done on SPSS version 26.0. Quantitative variables were presented as mean ± S.D. Qualitative variables, i.e., gender, types of myocardial infarction (STEMI/ NSTEMI), and patterns of left ventricular function (Abnormal/ moderately to severely impaired) were presented as frequency and percentage. Results: The average age of the cases in this study was 52.74 ± 8.08 years. There were 72 (65.5%) males and 38 (34.5%) females enrolled in this study. The mean BMI, LVEF, and duration of MI were 27.62 ± 4.27 (kg/m2), 35.30 ± 7.88 (%), and 176.18 ± 5.65 (minutes). There were 35 (31.8%) patients diagnosed with STEMI and 75 (68.2%) diagnosed with NSTEMI. There were 40 (36.4%) patients found with abnormal LVEF patterns and 70 (63.6%) with moderately to severely impaired LVEF. Conclusion: The results of this study showed that the majority of patients with acute MI had moderately to severely impaired LVEF.